2011
DOI: 10.1002/tox.20662
|View full text |Cite
|
Sign up to set email alerts
|

Rutin inhibits human leukemia tumor growth in a murine xenograft model in vivo

Abstract: Numerous studies have shown that rutin has anticancer effects. We have previously reported that rutin induced cell cycle arrest and apoptosis in murine leukemia WEHI-3 cells in vitro and in vivo. However, there are no data showing that rutin inhibits human leukemia HL-60 cells in vivo in a murine xenograft animal model. Human leukemia HL-60 cells were implanted into mice and treated with vehicle (1% DMSO), rutin (120 mg/kg of body weight) or vinblastine (120 μg/kg of body weight). Compounds and agents were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 21 publications
0
79
0
2
Order By: Relevance
“…In fact, it has been demonstrated that rutin causes cell cycle arrest and induces apoptosis in many types of human cancer cell lines (La Casa, Villegas, Alarcon de la Lastra, Motilva, & Martin Calero, 2000;Lin et al, 2009). On the other hand, some works have indicated that the enzymatic polymerisation of rutin might improve its biological activities (Anthoni et al, 2008;Kurisawa, Chung, Uyama, & Kobayashi, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, it has been demonstrated that rutin causes cell cycle arrest and induces apoptosis in many types of human cancer cell lines (La Casa, Villegas, Alarcon de la Lastra, Motilva, & Martin Calero, 2000;Lin et al, 2009). On the other hand, some works have indicated that the enzymatic polymerisation of rutin might improve its biological activities (Anthoni et al, 2008;Kurisawa, Chung, Uyama, & Kobayashi, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, attention has focussed on the identification of antimutagenic and/or anticarcinogenic effects of these polyphenols in animal systems (Lin et al, 2009). The mutagenic and antimutagenic activities of monomeric polyphenols were reported by some authors (Chulasiri, Bunyapraphatsara, & Moongkarndi, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…WEHI-3 cells at the density of 5x10 4 cells/well were plated on 4-well chamber slides and were then treated without (control) or with 300 µM of GA for 24 h. At the end of incubation, cells were washed with PBS and fixed with 4% formaldehyde in PBS for 15 min, followed by permeabilization for 1 h using 0.3% Triton X-100 in PBS containing 2% BSA for blocking non-specific binding sites. Cell samples were then stained by anti-AIF, anti-Endo G or anti-cytochrome c antibodies (1:100 dilution, respectively) for 24 h, washed twice with PBS and then stained with a secondary antibody (FITC-conjugated goat anti-mouse IgG at 1:100 dilution) for 40 min, followed by PI staining for DNA analysis.…”
Section: Western Blot Analysis For Examining the Associated Protein Lmentioning
confidence: 99%
“…According to the Department of Health, Executive Yuan, Taiwan R.O.C. (2010), approximately 4.2 per 100,000 people in Taiwan succumb to leukemia each year (3,4). Currently, treatment of leukemia in clinics includes hematopoietic stem cell transplantation, radiotherapy and chemotherapy agents; however, these outcomes are not fully satisfactory (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ellagic acid, rutin and quercetin were found to be major polyphenolic compounds. The antioxidant and anticancer properties of these compounds have been well established [ 28,29,30,31,32 ]. The high level of protective activities imparted by these compounds serves as an evidence for the importance of AME extract in ameliorating the oxidative stress.…”
Section: Discussionmentioning
confidence: 99%